MeioBase: a comprehensive database for meiosis - Li, Hao; Meng, Fanrui; Guo, Chunce; Wang, Yingxiang; Xie, Xiaojing; Zhu, Tiansheng; Zhou, Shuigeng; Ma, Hong; Shan, Hongyan; Kong, Hongzhi (Frontiers in Plant Science, 2014)
Meiosis is a special type of cell division process necessary for the sexual reproduction of all eukaryotes. The ever expanding meiosis research calls for an effective and specialized database that is not readily available yet. To fill this gap, we have developed a knowledge database MeioBase (http://meiosis.ibcas.ac.cn), which is comprised of two core parts, Resources and Tools. In the Resources part, a wealth of meiosis data collected by curation and manual review from published literatures and biological databases are integrated and organized into various sections, such as Cytology, Pathway, Species, Interaction, and Expression. In the Tools part, some commonly used tools have been integrated into MeioBase, such as Search, Download, Blast, Comparison, My Favorites, Submission, and Advice. With a simplified and efficient web interface, users are able to search against the database with gene model IDs or keywords, and batch download the data for local investigation. We believe that MeioBase can greatly facilitate the researches related to meiosis.